Electrode and power storage device

The electrode design with a controlled carbon nanotube network and binder improves mechanical strength, preventing cracks and ensuring electrical continuity in lithium-ion batteries.

JP2025166629APending Publication Date: 2025-11-06NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024070794
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-11-06

AI Technical Summary

Technical Problem

The volume change of active materials in lithium-ion secondary batteries can cause cracks in the electrode, disrupting the conductive network and leading to electrical isolation of active materials.

Method used

An electrode comprising a composite layer with a specific ratio of carbon nanotube ends per unit volume, bound by a binder with a tensile strength of 60 N/mm², which reduces the occurrence of cracks by maintaining a robust carbon nanotube network.

Benefits of technology

The carbon nanotube network, combined with a suitable binder, enhances the mechanical strength of the composite layer, preventing cracks and maintaining electrical connectivity during volume changes of the active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025166629000001_ABST
    Figure 2025166629000001_ABST
Patent Text Reader

Abstract

To provide an electrode and a power storage device capable of reducing crack generation.SOLUTION: The electrode includes a current collector and a composite layer attached to the current collector. The composite layer includes an active material, carbon nanotubes, and a binder, and the active material contains silicon. The ratio of the number of end portions of the carbon nanotubes per unit volume of the composite layer is 8.0×109 / cm3 to 3.2×1011 pieces / cm3. The power storage device includes a positive electrode and a negative electrode.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an electrode and an electricity storage device that include an active material and carbon nanotubes. [Background technology]

[0002] Lithium-ion secondary batteries (electricity storage devices) are known that include a negative electrode (electrode) containing a silicon-containing active material and carbon nanotubes. In the prior art disclosed in Patent Document 1, the carbon nanotubes electrically connect the active materials to prevent the conductive network between the active materials from being cut off due to volume changes in the active materials caused by the absorption and release of lithium ions, resulting in no active materials being electrically isolated. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-110876 Summary of the Invention [Problem to be solved by the invention]

[0004] In the prior art, the volume change of the active material can cause cracks in the electrode.

[0005] The present invention has been made to solve this problem, and has an object to provide an electrode and an electricity storage device that can reduce the occurrence of cracks. [Means for solving the problem]

[0006] To achieve this object, a first aspect of the present invention is an electrode comprising a current collector and a composite layer attached to the current collector, the composite layer comprising an active material, carbon nanotubes, and a binder, the active material comprising silicon, and a ratio of the number of carbon nanotube ends per unit volume of the composite layer being 8.0×10 9 pieces / cm 3 Over 3.2 x 10 11pieces / cm 3 The following is the result.

[0007] In the second embodiment, the binder is a binder having a tensile strength of 60 N / mm at a pulling speed of 5 mm / min. 2 That's all.

[0008] A third aspect is the first or second aspect, wherein the binder is polyacrylic acid or polyacrylamide.

[0009] In a fourth aspect, in any one of the first to third aspects, the active material has a silicon content of 10% by mass or more and 50% by mass or less.

[0010] A fifth aspect is an electricity storage device, which includes a positive electrode and a negative electrode, and the negative electrode is the electrode according to any one of the first to fourth aspects. [Effects of the Invention]

[0011] According to the present invention, the composite layer attached to the current collector contains an active material containing silicon, carbon nanotubes, and a binder. The ratio of the number of carbon nanotube ends per unit volume of the composite layer is 8.0×10 9 pieces / cm 3 Over 3.2 x 10 11 pieces / cm 3 Since the carbon nanotube network is less than 100%, the occurrence of cracks can be reduced by the binder-bound carbon nanotube network. [Brief explanation of the drawings]

[0012] [Figure 1] 1 is a cross-sectional view of an electricity storage device according to an embodiment. DETAILED DESCRIPTION OF THE INVENTION

[0013] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Fig. 1 is a schematic cross-sectional view of an electricity storage device 10 according to one embodiment. The electricity storage device 10 includes, in order, a negative electrode 11, a separator 14, and a positive electrode 15. The electricity storage device 10 is an element that converts chemical energy into electrical energy and vice versa.

[0014] 1 illustrates an electricity storage device 10 having one set of a negative electrode 11, a separator 14, and a positive electrode 15, but the invention is not limited to this and may include a plurality of sets of these. The electricity storage device 10 is not limited to one having a stacked structure, but may also have a wound structure in which the negative electrode 11 and the positive electrode 15 are stacked with the separator 14 interposed therebetween and wound.

[0015] Examples of the electricity storage device 10 include a lithium ion battery and a lithium ion capacitor. Examples of lithium ion capacitors include redox capacitors that utilize a redox reaction of an electrode or a redox reaction of ions in a non-aqueous electrolyte, and hybrid capacitors that combine an electric double layer and a redox reaction, or that combine them with a secondary battery material.

[0016] The negative electrode 11 includes a current collector 12 and a composite layer 13 attached to the current collector 12. There are no particular limitations on the material of the current collector 12, and examples include Cu, Al, a Cu alloy, an Al alloy, and stainless steel. There are also no particular limitations on the shape of the current collector 12. The current collector 12 may be a porous foil having a plurality of holes penetrating the current collector 12.

[0017] The composite layer 13 contains a silicon-containing active material, carbon nanotubes, and a binder. The active material is not limited as long as it can absorb and release lithium ions, except that it contains silicon. The silicon-containing active material may be Si, a Si-Li alloy, or a compound containing Si and O as constituent elements (hereinafter referred to as "SiO x " where 0.5≦X≦1.5 is an example.

[0018] SiO xSilicon oxide (SiO) is an oxide of silicon, and is exemplified by those having a structure in which microcrystalline or amorphous silicon is dispersed in an amorphous SiO matrix. x Since SiO has poor conductivity, x A conductive layer is provided to cover the surface of SiO x It is preferable to combine SiO with a conductive material. x Granulation is an example of a method for combining the conductive layer with the conductive material. Examples of the material for the conductive layer include metals such as Pt and Os, and carbon. Examples of the conductive material include graphite, low-crystalline carbon, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon black, carbon nanotubes, carbon fiber, and fibrous or coiled metals.

[0019] The active material may further include a carbon-based active material, examples of which include graphite, low-crystalline carbon, graphitizable carbon, non-graphitizable carbon, and carbon black.

[0020] The proportion of silicon in the active material is preferably 10% by mass or more and 50% by mass or less. In the electricity storage device 10 using lithium ions as a charge carrier, the active material containing silicon has a Li metal reference potential (Li + / Li), so that a silicon content of 10 mass % or more can increase the capacity density. To reduce the volume change of mixture layer 13 due to the absorption and desorption of lithium ions, the silicon content of the active material is preferably 50 mass % or less.

[0021] The carbon nanotubes electrically connect the active materials so that the active materials are not isolated in the composite layer 13. Furthermore, the number Ne of carbon nanotube ends per unit volume of the composite layer 13 calculated by the following formula (1) is 8.0 × 10 9 pieces / cm 3 Over 3.2 x 10 11 pieces / cm 3 The reason is as follows: The network structure in which the binder is bound to the carbon nanotubes improves the mechanical strength of mixture layer 13, and reduces the occurrence of cracks in mixture layer 13 due to volumetric changes of the active material.

[0022] Ne=2·D·P / (ρ·A·L·100) …Equation (1) D: Density of the composite layer 13 (g / cm 3 ) P: Ratio (wt%) of carbon nanotubes in the composite layer 13 ρ: density of carbon nanotubes (= 1.3 g / cm 3 ) A: Cross-sectional area of ​​the carbon nanotube (cm 2 ) L: Length of carbon nanotube (cm)

[0023] D in formula (1) is calculated by taking an image of the cross section of the composite layer 13 using a scanning electron microscope (SEM), calculating the area of ​​each material constituting the composite layer 13 relative to the area of ​​the image, and then considering the ratio of the area of ​​each material as the volume ratio (volume ratio). The volume ratio is multiplied by the known density of each material to calculate the density (g / cm 3 )

[0024] In formula (1), P is the ratio of the mass of the carbon nanotubes contained in the mixture layer 13 to the total mass of the materials constituting the mixture layer 13. ρ in formula (1) is the known density of the carbon nanotubes (=1.3 g / cm 3 )

[0025] A in equation (1) is the value obtained by multiplying the square of the radius, calculated using the outer diameter of the carbon nanotube as the diameter, by pi (cross-sectional area (cm 2 )). In equation (1), L is the length (cm) of one carbon nanotube. A and L can be obtained by taking an SEM image of the carbon nanotube, extracting several samples from the SEM image, measuring the diameter and length of the samples, and then taking the arithmetic average. The cross-sectional area and length listed in the carbon nanotube catalog or specifications can also be used as A and L.

[0026] In formula (1), the value of D·P / (ρ·A·L·100) is multiplied by 2 because one carbon nanotube has two ends. Therefore, formula (1) can be used to calculate the number of carbon nanotube ends per unit volume of composite layer 13.

[0027] The binder binds the active material and carbon nanotubes together. Examples of binders include fluororesins, acrylic resins, polyolefins, and rubbers. Examples of fluororesins include polytetrafluoroethylene, polyvinylidene fluoride, and vinylidene fluoride-hexafluoropropylene copolymers. Examples of acrylic resins include polyacrylic acid, polyacrylonitrile, and polyacrylamide. Examples of polyacrylic acid include polymethacrylic acid esters, polyacrylic acid esters, and sodium polyacrylate. Examples of polyolefins include polyethylene and polypropylene. Examples of rubber include styrene-butadiene rubbers. Polyacrylic acid or polyacrylamide, which have high tensile strength, is suitable as the binder.

[0028] The binder has a tensile strength of 60 N / mm at a pulling speed of 5 mm / min. 2 This is preferable because it improves the mechanical strength of the network structure in which the binder is bound to the carbon nanotubes. The binder film is a test piece obtained by creating a film of approximately uniform thickness using a solution in which the binder is dissolved in a solvent, and then evaporating the solvent by natural drying. The test piece has gripping portions at both ends of the gauge section that can be attached to the chuck of the tensile tester. The gauge section is a square plate with a length of 10 mm, a width of 10 mm, and a thickness of 3 mm or less. The test piece can be formed by pouring the solution into a test piece mold, or the film can be formed and then cut out to the size of the test piece.

[0029] To determine the tensile strength, the test piece is attached to the chuck of the tensile testing machine, and then the chuck is pulled away at a rate of 5 mm / min to apply a tensile force in the longitudinal direction of the gauge section, and the maximum tensile force (N) is measured. 2 ) is the value obtained by dividing the maximum tensile force by the cross-sectional area of ​​the gauge section before the tensile force is applied.

[0030] The ratio of carbon nanotubes to binder contained in composite layer 13 is preferably such that the ratio (mass%) of carbon nanotubes to composite layer 13 divided by the ratio (mass%) of binder to composite layer 13 is 0.006 or more and 0.27 or less. This is to create a network structure in composite layer 13 in which the binder is bound to the carbon nanotubes.

[0031] Positive electrode 15 is formed by stacking current collector 16 and composite layer 17. Examples of the material for current collector 16 include a metal selected from Ni, Ti, Fe, and Al, an alloy containing two or more of these elements, and stainless steel.

[0032] The composite layer 17 contains an active material such as graphite or activated carbon, and a conductive agent. Examples of the conductive agent include carbon black, acetylene black, ketjen black, and carbon fiber. The active material may be any material that can reversibly support anions, and is not limited to graphite or activated carbon.

[0033] A binder or a thickener that binds the active material and the conductive agent may be contained in the mixture layer 17. An example of the thickener is carboxymethyl cellulose.

[0034] The separator 14 is made of a porous material that is durable against the active materials and electrolyte solution contained in the negative electrode 11 and the positive electrode 15, and that is non-electron-conductive but allows lithium ions to pass through. Examples of the separator 14 include nonwoven fabrics and porous films made of cellulose, polypropylene, polyethylene, polyimide, alumina, etc.

[0035] The electrolyte solution contains a lithium salt dissolved in a solvent. The lithium salt is a compound used to transfer lithium ions between the negative electrode 11 and the positive electrode 15. The anion of the lithium salt is a halide ion (I - , Cl - , Br - etc.), SCN - , BF4 - , BF3(CF3) - , BF3(C2F5) - , PF6- , ClO4 - , SbF6 - , N(SO2F)2 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , B(C6H5)4 - , B(O2C2H4)2 - , C(SO2F)3 - , C(SO2CF3)3 - , CF3COO - , CF3SO2O - , C6F5SO2O - , B(O2C2O2)2 - is exemplified.

[0036] The solvent for the electrolyte solution is not particularly limited as long as it is liquid in the temperature range in which the electricity storage device 10 is used. Examples of the solvent include carbonate esters, aliphatic carboxylic acid esters, phosphate esters, γ-lactones, ethers, nitriles, sulfolane, dimethyl sulfoxide, fluorous solvents, and ionic liquids. A mixture of these solvents is also acceptable.

[0037] The electricity storage device 10 is manufactured, for example, as follows. A slurry is prepared by dispersing an active material and carbon nanotubes in a solution in which a binder is dissolved. A dispersion medium such as an organic solvent such as N-methyl-2-pyrrolidone or water, or a thickener may be added to the slurry. The prepared slurry is applied to the current collector 12, and then dried to obtain the negative electrode 11 in which the composite layer 13 is formed on the current collector 12. The dried composite layer 13 may be rolled using a roller or the like.

[0038] Next, Li is supplied to negative electrode 11, and lithium ions are pre-doped in an amount corresponding to at least a portion of the irreversible capacity. Pre-doping can be exemplified by a method in which current collector 12 and metallic lithium are short-circuited with a separator disposed between composite layer 13 and metallic lithium, and negative electrode 11, the separator, and metallic lithium are immersed in an electrolyte solution. Electrons flow from metallic lithium to current collector 12 due to the potential difference between current collector 12 and metallic lithium, and at the same time, the metallic lithium is ionized and released into the electrolyte solution, and the lithium ions in the electrolyte solution are supported by composite layer 13.

[0039] Pre-doping with lithium ions results in a negative electrode 11 in which the mixture layer 13 is lithiated. During the pre-doping, a current may be passed between the current collector 12 and metallic lithium. The lithiation of the mixture layer 13 means that some of the atoms constituting the mixture layer 13 have been replaced with lithium atoms, that is, the mixture layer 13 contains lithium.

[0040] Next, a slurry is prepared by dispersing an active material and a conductive agent in a solution in which a binder has been dissolved. The slurry is applied onto a current collector 16 and then dried, resulting in a positive electrode 15 in which a composite layer 17 is formed on the current collector 16. The separator 14, positive electrode 15, and negative electrode 11 are each cut to a predetermined shape, and then the positive electrode 15, separator 14, and negative electrode 11 are stacked in this order. Terminals (not shown) are connected to the current collectors 12 and 16, respectively, and the resulting product is sealed in a case (not shown) together with an electrolyte to obtain an electricity storage device 10. [Example]

[0041] The present invention will be explained in more detail with reference to examples, but the present invention is not limited to these examples.

[0042] (Measurement of binder tensile strength) Polyacrylic acid (binder) and pure water were mixed in a mixer and coated onto a polyethylene terephthalate film. Air-drying at room temperature for 24 hours produced a binder film approximately 2 mm thick. After cutting the film into a rectangle 30 mm long and 10 mm wide, a 10 mm long gauge section was left. Adhesive tape was attached to the 10 mm long sections on both ends of the gauge section to reinforce them and serve as gripping sections, yielding a test specimen. The thickness of the gauge section was measured, and the cross-sectional area of ​​the gauge section was calculated. Test specimens were similarly prepared using polyacrylamide and styrene butadiene rubber (SBR) (both binders).

[0043] The gripping part of the test piece was attached to a pair of chucks of a tensile testing machine (SL-6001 manufactured by Imada Seisakusho Co., Ltd.), and the chucks were moved at a speed of 5 mm / min to apply a tensile force to the gauge part, and the maximum tensile force when the gauge part broke was measured. The maximum tensile force was divided by the cross-sectional area of ​​the gauge part to determine the tensile strength of the binder (N / mm 2 The tensile strength of polyacrylic acid was 60 N / mm 2 The tensile strength of polyacrylamide is 80N / mm 2 and the tensile strength of SBR is 5N / mm 2 It was.

[0044] (Pre-doping of negative electrode) Carbon-coated silicon particles (silicon-containing active material), carbon nanotubes, a binder, and carboxymethyl cellulose (a thickener) were mixed in pure water and mixed in a mixer to prepare a slurry. Various slurries were prepared by varying the amounts of the active material, carbon nanotubes, binder, and thickener to obtain a total of 100 parts by weight, with the ratios being 80-95 parts by weight of the active material, 0.01-4 parts by weight of the carbon nanotubes, 3-10 parts by weight of the binder, and 1 part by weight of the thickener.

[0045] The active material was fabricated by varying the ratio of silicon to carbon covering the silicon. Carbon nanotubes with a diameter of 8 nm and a length of 35 μm and those with a diameter of 8 nm and a length of 2000 μm were used. The binder used was polyacrylic acid, polyacrylamide, or SBR.

[0046] The slurry was applied to a current collector made of 8 μm-thick copper foil and vacuum dried at 70°C for 1 hour to prepare various negative electrodes. The total mass of the slurry, including the active material, carbon nanotubes, binder, and thickener, was 4.6 mg / cm. 2 In this way, the negative electrode of Sample No. 1-22 was obtained.

[0047] A half-cell was fabricated by sequentially attaching a separator and a metallic lithium foil (counter electrode) pressed onto copper foil on top of a composite layer of a negative electrode punched into a square with a side length of 25 mm. The half-cell was immersed in the electrolyte, then vacuum degassed and sealed. A current was passed between the copper foil current collector of the half-cell and the copper foil counter electrode, and pre-doping was performed by charging at a constant current of 0.1 C to 0 V at 25 °C, followed by constant voltage charging to 0.01 C. The electrolyte was a solution of lithium bis(fluorosulfonyl)imide (LiFSI) as a lithium salt (1 mol / dm 3 ) was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate.

[0048] (judgement) After removing the lithiated negative electrode from the half cell, the composite layer was visually observed. Samples in which cracks did not occur in the composite layer were judged as A, and samples in which cracks occurred in the composite layer were judged as B. The number of carbon nanotube (CNT) ends (10 9 pieces / cm 3 ), tensile strength of binder (N / cm 3 ), the percentage of silicon in the active material (mass %), and the evaluation are shown in Table 1.

[0049] [Table 1]

[0050] As shown in Table 1, the number of CNT ends was 8.0 × 10 9 pieces / cm 3 Over 3.2 x 10 11 pieces / cm 3 Sample No. 2-19, which had a CNT end count of 8.0 × 10 or less, was judged to be A. 9 pieces / cm 3 Sample No. 1, in which the number of CNT ends was less than 3.2 × 10 11 pieces / cm 3 Sample No. 20-22, which exceeded 8.0 × 10 9 pieces / cm 3 Over 3.2 x 10 11pieces / cm 3 It was confirmed that if the thickness is less than this, even if the volume of the active material changes due to pre-doping, cracks do not occur in the composite layer. It is presumed that the mechanical strength of the composite layer of Sample No. 2-19 is improved by the network structure created by the carbon nanotubes.

[0051] Sample No. 2-19 has a binder tensile strength of 60 N / cm 3 The ratio of silicon in the active material was 10-50 mass %. According to the examples, the tensile strength of the binder was 60 N / cm 3 It was found that the mechanical strength of the composite layer can be ensured by the above and by setting the ratio of silicon in the active material to 10-50 mass %.

[0052] The present invention has been described above based on the embodiments, but the present invention is not limited to the above embodiments, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention.

[0053] In the embodiment, the electricity storage device 10 has been described as including a positive electrode 15 in which a composite layer 17 is provided on one surface of a current collector 16, and a negative electrode 11 in which a composite layer 13 is provided on one surface of a current collector 12, but the present invention is not necessarily limited to this. For example, it is of course possible to apply each element in the embodiment to an electricity storage device including electrode layers (so-called bipolar electrodes) in which a composite layer 13 and a composite layer 17 are provided on both surfaces of a current collector 12. If bipolar electrodes and separators 14 are alternately stacked and housed in a case (not shown), an electricity storage device with a so-called bipolar structure can be obtained.

[0054] In the embodiment, the negative electrode 11 is described in which the composite layer 13 is provided on one surface of the current collector 12, but this is not necessarily limited to this. It is of course possible to provide the composite layer 13 on both surfaces of the current collector 12.

[0055] In the embodiment, a lithium ion capacitor has been described as an example of the electricity storage device 10 including the negative electrode 11, but the present invention is not necessarily limited to this. Another electricity storage device including the negative electrode 11 is a lithium ion battery. Examples of lithium ion batteries include those in which an electrolytic solution passes through the separator 14, those in which the separator 14 is made of a solid electrolyte, those in which the separator 14 contains a polymer or gel electrolyte, and those in which the separator 14 contains clay composite layers 13, 17. [Explanation of symbols]

[0056] 10. Energy storage devices 11 Negative electrode (electrode) 12 Current collector 13 Mixed material layer 15 Positive electrode

Claims

1. a current collector; and a composite layer attached to the current collector, the composite layer includes an active material, carbon nanotubes, and a binder; The active material is an electrode containing silicon, The ratio of the number of ends of the carbon nanotubes per unit volume of the composite layer is 8.0 × 10 9 pieces / cm 3 3.2 x 10 11 pieces / cm 3 The electrodes are as follows:

2. The binder has a tensile strength of 60 N / mm at a pulling rate of 5 mm / min. 2 The electrode according to claim 1, wherein

3. 3. The electrode of claim 2, wherein the binder is polyacrylic acid or polyacrylamide.

4. 4. The electrode according to claim 1, wherein the active material contains silicon in an amount of 10% by mass or more and 50% by mass or less.

5. An electricity storage device including a positive electrode and a negative electrode, The electric storage device, wherein the negative electrode is the electrode according to claim 1 .

Citation Information

Patent Citations

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2016110876A